2021
DOI: 10.1177/0300060520984916
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes of tuberculosis patients and associated factors in Bale Zone, Southeast Ethiopia: a retrospective study

Abstract: Objective This study assessed the outcome of tuberculosis treatment and associated factors in Bale Zone, Southeast Ethiopia in 2017. Methods This was 5-year retrospective study of a health registry for tuberculosis patients, which was reviewed from 1 September 2011 to 30 August 2016. Data were analyzed, and descriptive and logistic regression analyses were used to identify the factors that were associated with tuberculosis treatment outcomes. Results Among the 7205 tuberculosis patients, 6325 (87.8%) had a suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 15 publications
(28 reference statements)
2
9
2
Order By: Relevance
“…It was observed that TB patients within the age groups 20 to 35 years old were more likely to have successful treatment outcome compared the patients older than 35 years old. This findings were consistent with the report from other studies from Southeast Ethiopia, [39] Eastern Ethiopia, [13] Northeast Ethiopia, [21] Southeast Ethiopia, [40] Ghana [16] and Central Ethiopia. [12] On the other hand, the findings of our study were not in agreement with several studies reported no association of age with treatment outcome from Debre Tabor General Hospital in Northwest Ethiopia, [26] Jinka, [19] and Southern Ethiopia.…”
Section: Discussionsupporting
confidence: 93%
“…It was observed that TB patients within the age groups 20 to 35 years old were more likely to have successful treatment outcome compared the patients older than 35 years old. This findings were consistent with the report from other studies from Southeast Ethiopia, [39] Eastern Ethiopia, [13] Northeast Ethiopia, [21] Southeast Ethiopia, [40] Ghana [16] and Central Ethiopia. [12] On the other hand, the findings of our study were not in agreement with several studies reported no association of age with treatment outcome from Debre Tabor General Hospital in Northwest Ethiopia, [26] Jinka, [19] and Southern Ethiopia.…”
Section: Discussionsupporting
confidence: 93%
“…We obtained a mortality rate of 10.2%, but in different studies [ 17 ], it varies greatly [ 18 ]. There is no significant difference in terms of mortality between those who receive the diagnosis during admission or before admission.…”
Section: Discussionmentioning
confidence: 99%
“…The Weibull distribution is suitable for modeling data with monotone hazard rates that increase or decrease exponentially over time. For Weibull regression, λ is the scale parameter and γ is a shape parameter, and its probability distribution function shown below [4] Expressing the latent field x, in terms of the predictor , the standard Weibull regression is expressed and ( ) , 0…”
Section: Exponential Distributionmentioning
confidence: 99%
“…TB control is a serious public health priority in many low and middle income countries (LMIC) as death rates among patients on TB treatment is still increasing globally (3,4). Several factors affecting survival of patients are missed in the TB treatment programs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation